The impact of academic resource sharing on university development and talent training in Heilongjiang Province, Chi - Donglai, Shi; Hamid, Junainah Abd; Tham, Jacquline (Edelweiss Applied Science and Technology, 2025)
Against the backdrop where academic resource sharing emerges as a pivotal driver for university development and talent cultivation, this study delves into its impact on universities in Heilongjiang Province, China. Data were collected from three representative institutions—Harbin Engineering University, Qiqihar University, and Heihe University. Employing quantitative approaches involving SPSS and AMOS, it analyzed the correlation between academic resource sharing and university development. Findings indicate that such sharing significantly enhances universities’ research capabilities, spurs interdisciplinary collaboration, and improves teaching quality. It also optimizes talent cultivation by providing extensive high-quality learning materials, faculty expertise, and international academic networks. However, challenges like uneven resource distribution, administrative bottlenecks, and lack of institutional incentives impede its full potential. Consequently, this study proposes policy recommendations, including improving resource-sharing mechanisms, strengthening inter-university cooperation, and bolstering institutional support frameworks. These measures can contribute to the long-term development of universities and the establishment of a more innovative and globally competitive higher education system in Heilongjiang Province.